“I was not a nobody, but no one knew what I was”: A Mother’s Reclamation of her Story in Madhavi S. Mahadevan’s Bride of the Forest - J, Mruthula (Amaltea. Revista de Mitocrítica, 2024)
The ideological stronghold of mythology in the cultural consciousness necessitates the production of counter-ideologies that decenter the normative narrative with more subversive and progressive tales. The story of Madhavi from the Indian epic Mahabharata is upheld as a tale of a devoted daughter who is blessed with a privileged womb, which is prophesied to give birth to great kings, and a boon of chirkaumya, the ability to regain virginity. Devoid of any rights over her own body, Madhavi becomes instrumental for Gaalav, the disciple of Vishwamitra, in fulfilling his promise of eight hundred white horses with black-colored left ears as gurudakshina (tradition of repaying one’s teacher) to his teacher. Her womb is bartered, allowing men to exchange her indefinitely as a commodity with utilitarian value. Her voice, desires and feelings are undermined by the structural needs of the masculine tale. This paper seeks to read the novel Bride of the Forest by Madhavi. S. Mahadevan in the context of motherhood studies and postfeminism through the examination of the character Madhavi. It inquires into the representation of the maternal figures who are mapped on a power spectrum to posit that both agency and victimhood co-exist in uncomfortable ways.